The Relationship Between Peer Attachment and Emotion Regulation in Grade 12 Students at School: Hubungan Antara Peer Attachment dengan Regulasi Emosi Pada Siswi Kelas 12 di Sekolah - Chabibah, Siti; Affandi, Ghozali Rusyid (Psikologia : Jurnal Psikologi, 2022)
According to research by Bowlby [1], where the support figure attachment physically and emotionally can affect the development of adaptive emotion regulation. The purpose of this study was to see whether there was a relationship between peer attachment and emotional regulation in class XII students at school X. This study used a quantitative research type with a sample of 114 students sitting in bench XII. The sampling technique used is quota sampling with non-probability sampling technique. The scale used by the author for data collection uses the peer attachment scale which was developed by the author himself through the dimensions of peer attachment and the emotion regulation scale which was developed through aspects of emotion regulation with a total of 80 questions in the form of a Likert scale. The results showed that there was no relationship between peer attachment and emotional regulation in class XII students with a correlation coefficient of r=0.072 Sig 0.444 > 0.05. Then the researchers conducted a different test on the peer attachment scale with emotion regulation for each major. The results of the different peer attachment test with a value of F = 5.668 and sig (0.001) > 0.05 where there are differences for each major.